Perfluorooctane sulfonate (PFOS) and perfluorooctanoate (PFOA) in soils and groundwater of a U.S. metropolitan area: Migration and implications for human exposure. (1st April 2015) - Xiao, Feng; Simcik, Matt F.; Halbach, Thomas R.; Gulliver, John S.
Abstract: Perfluorooctane sulfonate (PFOS) and perfluorooctanoate (PFOA) are emerging anthropogenic compounds that have recently become the target of global concern due to their ubiquitous presence in the environment, persistence, and bioaccumulative properties. This study was carried out to investigate the migration of PFOS and PFOA in soils and groundwater in a U.S. metropolitan area. We observed elevated levels in surface soils (median: 12.2 ng PFOS/g dw and 8.0 ng PFOA/g dw), which were much higher than the soil-screening levels for groundwater protection developed in this study. The measured levels in subsurface soils show a general increase with depth, suggesting a downward movement toward the groundwater table and a potential risk of aquifer contamination. Furthermore, concentrations of PFOS and PFOA in monitoring wells in the source zone varied insignificantly over 5 years (2009–2013), suggesting limited or no change in either the source or the magnitude of the source. The analysis also shows that natural processes of dispersion and dilution can significantly attenuate the groundwater contamination; the adsorption on aquifer solids, on the other hand, appears to have limited effects on the transport of PFOS and PFOA in the aquifer. The probabilistic exposure assessment indicates that ingestion of contaminated groundwater constitutes a much more important exposure route than ingestion of contaminated soil. Overall, the results suggest that ( i ) the transport of PFOS and PFOA is retarded in the vadose zone, but not in the aquifer; ( ii ) the groundwater contamination of PFOS and PFOA often follows their release to surface soils by years, if not decades; and ( iii ) the aquifer can be a major source of exposure for communities living near point sources. Graphical abstract: Highlights: Soil-screening levels for groundwater protection were developed. Migration from contaminated soil to groundwater acts as a major exposure pathway. Groundwater concentrations vary strongly in space, but the spatial pattern is stable. Drinking-water wells can be a major source of exposure to PFOS and PFOA. The environmental impact of historical waste disposal practices is long-lasting.